The Implementation of Protection and Empowerment of Female Migrant Workers (Study on The Independent Women Program of Perempuan Berdikari (Pe-Ri) in Indramayu Regency in 2021-2024) - Cahyono Cahyono; Ibrahim Ibrahim; Samugyo Ibnu Redjo; Novie Indrawati Sagita (ARISTO, 2026)
Empowering Indramayu migrant workers has an important and strategic role in increasing economic development and human resources. In reality, the role of empowering post-migrants through the Pe-Ribe Independent Women Program has not yet been maximally carried out by the regional government of Indramayu Regency. The method used in this research is qualitative. The collection is carried out. Interview techniques will be used as a tool in qualitative research. Information that is not recorded in documents, information from relevant events and personalities, namely interactive model analysis. The research results show that the implementation of protection and empowerment of former migrants in Indramayu Regency has not been optimal in the field, especially the issue of business capital assistance for former migrants, facilities are inadequate for implementation.